A Novel Hybrid Photonic Integration Scheme Based on Flip-Chip Bonding Combined With Vertical Coupling - Guojiong Li; Xiangyang Dai; Yuanhao Zhang; Liyuan Song; Panpan Yu; Minwen Xiang; Can Liu; Juan Xia; Qiaoyin Lu; Weihua Guo (IEEE Photonics Journal)
A hybrid photonic integration scheme based on flip-chip bonding combined with vertical coupling is presented in this work, offering a novel solution for the integration of active and passive chips. An offset quantum-well laser is flipped and bonded into the pre-set cavity of the passive chip. The light emitted from the laser propagates through a taper into the passive chip. The proposed scheme utilizes only the existing processes, eliminating the need for additional process development. Furthermore, it preserves the performance of the laser while providing high tolerance. Simulations indicate that the coupling tolerance for 90% coupling efficiency is approximately ±1.5 μm in the lateral direction with the longitudinal tolerance exceeding 20 μm. The coupling efficiency remains stable across the O-band. This scheme is adaptable for integrating various photonic chips such as tunable lasers, high-speed modulators and detectors, and laser radar systems.